Maneuvering Together, Apart, and at Odds: Residents' Care Convoys in Assisted Living. (1st February 2018) - Kemp, Candace L; Ball, Mary M; Morgan, Jennifer Craft; Doyle, Patrick J; Burgess, Elisabeth O; Perkins, Molly M
Abstract: Objectives: Frail and disabled individuals such as assisted living residents are embedded in "care convoys" comprised of paid and unpaid caregivers. We sought to learn how care convoys are configured and function in assisted living and understand how and why they vary and with what resident and caregiver outcomes. Method: We analyzed data from a qualitative study involving formal in-depth interviews, participant observation and informal interviewing, and record review. We prospectively studied 28 residents and 114 care convoy members drawn from four diverse assisted living communities over 2 years. Results: Care convoys involved family and friends who operated individually or shared responsibility, assisted living staff, and multiple external care workers. Residents and convoy members engaged in processes of "maneuvering together, apart, and at odds" as they negotiated the care landscape routinely and during health crises. Based on consensus levels, and the quality of collaboration and communication, we identified three main convoy types: cohesive, fragmented, and discordant. Discussion: Care convoys clearly shape care experiences and outcomes. Identifying strategies for establishing effective communication and collaboration practices and promoting convoy member consensus, particularly over time, is essential to the creation and maintenance of successful and supportive care partnerships.